Modeling the behavior of Geobacillus stearothermophilus ATCC 12980 throughout its life cycle as vegetative cells or spores using growth boundaries. (June 2015) - Mtimet, Narjes; Trunet, Clément; Mathot, Anne-Gabrielle; Venaille, Laurent; Leguérinel, Ivan; Coroller, Louis; Couvert, Olivier
Abstract: Geobacillus stearothermophilus is recognized as one of the most prevalent micro-organism responsible for flat sour in the canned food industry. To control these highly resistant spore-forming bacteria, the heat treatment intensity could be associated with detrimental conditions for germination and outgrowth. The purpose of this work was to study successively the impact of temperature and pH on the growth rate of G. stearothermophilus ATCC 12980, its sporulation ability, its heat resistance in response to various sporulation conditions, and its recovery ability after a heat treatment. The phenotypic investigation was carried out at different temperatures and pHs on nutrient agar and the heat resistance was estimated at 115 °C. The greatest spore production and the highest heat resistances were obtained at conditions of temperature and pH allowing maximal growth rate. The current observations also revealed that growth, sporulation and recovery boundaries are close. Models using growth boundaries as main parameters were extended to describe and quantify the effect of temperature and pH throughout the life cycle of G. stearothermophilus as vegetative cells or as spore after a heat treatment and during recovery. Highlights: Sporulation is more abundant at optimal growth conditions. The most heat resistant spores are produced at optimal growth conditions. Spores formed at 45 °C are four time less resistant than spores formed at 57 °C. Sporulation and recovery occurred only in temperature and pH range allowing growth. Growth boundaries could be used to predict heat resistance and recovery.